The influence of friends on teenage offending: How long does it last?. (January 2013) - Smith, David J.; Ecob, Russell
This study focuses on the question whether peers have a lasting effect on offending behaviour. In a longitudinal study of 4300 teenagers in Edinburgh, Scotland, respondents nominated three friends at age 13–14 most of whom were identified as other members of the cohort. The growth curve of own offending was modelled over a period of three years from age 13–14. By allowing for the effect of own prior offending on the friendship network, the model specifies the influence running from friends to self. The level of offending of the three friends nominated at age 13–14 has a clear immediate effect on own offending, which steadily diminishes over time but remains statistically significant for a period of four to five years in a 'slim' model of broad offending and for two to three years in a 'fatter' model that adjusts for a wide range of explanatory variables. Many of these other variables have a significant influence on the growth curve of offending, but friends' offending is among the most important variables explaining own offending. It is argued that social learning about the techniques, pleasures and justifications of offending may be important in explaining the persisting influence of friends, whereas situational factors and peer pressure may be important in explaining their immediate, short-term influence.